Development of Beach Tourism Destinations by Village-Owned Enterprises (Bumdesa) in Buru Regency Maluku Province - Khairunnisa Salsabila Sahadi; Gatiningsih Gatiningsih; Haikal Ali (Sean Institute, 2026)
Tourism sector development has become one of the efforts made by local governments to enhance economic growth and increase Regional Original Revenue (PAD). Buru Regency possesses considerable natural tourism potential; however, the contribution of the tourism sector to regional revenue remains relatively low. One of the tourism development efforts has been carried out through the involvement of Village-Owned Enterprises (BUMDesa) in managing tourism destinations based on local potential. This study aims to analyze the development of beach tourism destinations by BUMDesa in Buru Regency, focusing on the management of Baikolet Beach Tourism by BUMDesa Jikumerasa. This research applies the tourism destination development theory proposed by Sunaryo (2013), which includes the dimensions of tourist attractions and appeal, accessibility, amenities, supporting infrastructure, other supporting tourism facilities, as well as tourism institutions and human resources. This study employs a descriptive qualitative research method. Data collection techniques were conducted through interviews, observation, and documentation. The data were analyzed using the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the development of the Baikolet Beach tourism destination by BUMDesa Jikumerasa has generally been implemented quite well. However, the development of the tourism destination still requires improvement in several dimensions. The dimensions that need primary attention are tourism institutions and human resources, tourist attractions and appeal, and other supporting tourism facilities. Tourism management has not been fully supported by optimal institutional coordination, clear task distribution, managerial capacity of the management team, and structured tourism promotion. In addition, the development of tourism attractions remains limited, and supporting facilities such as culinary services, souvenir products, and security supervision are still not optimal.